Frequently asked questions : market access for (non-agricultural) goods, Barbados - Schloemann, Hannes (Ministry of Foreign Affairs and Foreign Trade. Foreign Trade Division St. MichaelBB, 2007)
Provides brief answers to some of the more frequently asked questions on World Trade Organization (WTO) agreements concerning market access for (non-agricultural) goods. Deals with issues ranging from the basic principles of the World Trade Organization to the WTO rules in goods and new developments which affect international rules in theis area.